A case study on lexical and morphosyntactic skills in multilingual autism - Kambanaros, Maria; Theodorou, Eleni; Grohmann, Kleanthes K. (My University, 2013)
This paper reports lexical and morphosyntactic abilities of a 9-year-old boy with high functioning autism. With a Russian mother and a Greek Cypriot father, the participant, Y.S., is a native speaker of Russian and Cypriot Greek, while Standard Modern Greek was acquired upon early school entry at age 4. METHODS Y.S. was assessed on three measures tapping into lexical access via picture confrontation naming: the Vocabulary subtest of the Developmental Verbal Intelligence Quotient (Stavrakaki & Tsimpli, 2000), the standardized Greek version of the Renfrew Word Finding Vocabulary Test (Sideris, 2009; original: Renfrew, 1997), and the Cypriot Object and Action Test (Kambanaros et al., 2012; original: Kambanaros, 2003). His lexical abilities were further examined using the Definition subtest of the Athina Test (Paraskevopoulos et al., 1999). Morphosyntactic abilities were assessed using the DVIQ subtests Morphosyntactic Comprehension and Production. In addition, Y.S.’s performance on the following three measures of our own Greek adaptation of the Bus Story Test (Renfrew, 1997) was considered: number of subordinates, five longest sentences, and MLU-word. Moreover, Y.S. was assessed on the metalinguistic and sentence repetition subtests of the DVIQ, on the Raven’s Coloured Progressive Matrices (Raven et al., 2000), on the Greek version of the Peabody Picture Vocabulary Test (Simos et al., 2011; original: Dunn & Dunn, 1981), the Phoneme Discrimination subtest of the Athina Test (Paraskevopoulos et al., 1999), and on our own Greek adaptation of the Concept–Word Association Test (in collaboration with Naama Friedmann). Finally, his teacher completed the Greek version of the Strengths and Difficulties Questionnaire (Goodman, 1997), describing Y.S.’s behavior in the classroom and with peers. RESULTS Y.S.’s performance on the measures conducted reveal a significant discrepancy between comprehension and production, with comprehension relatively intact, while production is severely impaired for both lexicon and morphosyntax. DISCUSSION We will present our results for Y.S. using a multiple case study approach where his performance will be compared to both multilingual and bilectal Cypriot Greek (L1)–Standard Modern Greek (L2) male individuals with and without specific language impairment (SLI), matched on non-verbal performance who have been tested on all the measures reported above. Our findings will be discussed in relation to the Autism as SLI Plus Hypothesis (Bishop, 2003) with reference to psycholinguistic models of multilingualism (Marini & Fabbro, 2007).
Keywords: Lexical abilities; Morphosyntactic abilities; Autism